1982
DOI: 10.2527/jas1982.553590x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Energy Intake during Lactation on the Interval from Weaning to Firts Estrus in Sows

Abstract: A total of 191 crossbred sows were used to determine the effect of energy intake during one lactation on (1) sow and pig performance and (2) the percentage of sows in estrus by 7, 14, 21 and 70 d postweaning. Sows received 8 (Lo) or 16 (Hi) Mcal of metabolizable energy (ME)/d (Exp. 1 and 2) and 8 (Lo), 12 (Md) or 16 (Hi) Mcal of Me/d (Exp. 3) during a 28-d lactation period. All sows were fed an equal amount of crude protein, vitamins and minerals that met or exceeded the recommendations of the National Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
2
3

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(56 citation statements)
references
References 28 publications
5
46
2
3
Order By: Relevance
“…Hence, almost all of the additional nutrients available to the sows were directed toward tissue anabolism (see Clowes et al, 1998 for further discussion) and could have potentially ameliorated any inhibitory effects of lactational catabolism on reproductive performance. Consistent with the data reported by Nelssen et al (1985), Mullan and Williams (1989), and Koketsu et al (1996), restriction of feed intake during lactation seemed to decrease litter weight at weaning and extended the weaning-to-estrus interval (Reese et al, 1982;Mullan and Williams, 1989). Despite the increase in body weight and backfat during lactation, the fertility of SA sows was not different from that of Table 3.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Hence, almost all of the additional nutrients available to the sows were directed toward tissue anabolism (see Clowes et al, 1998 for further discussion) and could have potentially ameliorated any inhibitory effects of lactational catabolism on reproductive performance. Consistent with the data reported by Nelssen et al (1985), Mullan and Williams (1989), and Koketsu et al (1996), restriction of feed intake during lactation seemed to decrease litter weight at weaning and extended the weaning-to-estrus interval (Reese et al, 1982;Mullan and Williams, 1989). Despite the increase in body weight and backfat during lactation, the fertility of SA sows was not different from that of Table 3.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, although the weaning-toestrus interval was not different between AL and SA sows, when estrus occurred SA sows were in a negative energy balance. If the situation between weaning and estrus was analogous to that of lactation, a sow approaching a more catabolic state would be expected to exhibit an extended weaning-to-estrus interval (Reese et al, 1982;Armstrong et al, 1986;Koketsu et al, 1996). However, data from King and Williams (1984) have shown that the weaning-toestrus interval cannot be reduced by additional feed consumption after weaning, and conversely, restriction of feed intake after weaning in sows that were fed 6 kg during lactation did not extend the time to return to estrus (Baidoo et al, 1992).…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, the intake of nutrients had a significant effect on WEI. Sows supplied with 71 MJ DE daily had a significantly shorter wean-to-estrus period than sows provided with 35 MJ DE daily (Reese et al 1982). x E 0energy main effect, L 0lysine main effect, E )L 0energy)lysine interaction.…”
Section: Discussionmentioning
confidence: 87%
“…Reese et al [15] did not find any effect of energy intake together with the feed on haematocrit value but they observed its differentiation between pregnancy and lactation.…”
Section: Discussionmentioning
confidence: 99%